Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Rawat Jalan di Puskesmas Kepanjenkidul Blitar - Abdul Aziz Al Kaharudin; Dhiptya Ratri Anggraheni (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this research is to determine the influence of the five dimensions of service quality on patient satisfaction, both partially and simultaneously. And to find out which variables have the most dominant influence on satisfaction. The research was conducted at the Outpatient Health Center Kepanjenkidul Blitar. The method used in this research is quantitative. The independent variables in this research are Tangible, Emphaty, Responsiveness, Reability, and Assurance. The dependent variable is patient satisfaction. The analysis method used is Multiple Linear Regression and uses SPSS version 20 for Windows statistical analysis tools. The results found that all variables had a positive and significant influence, both partially and simultaneously. The Empathy variable is the variable that has the dominant influence on satisfaction.